The effect of daily oral PrEP use during pregnancy on bone mineral density among adolescent girls and young women in Uganda - Zewdie, Kidist; Kiweewa, Flavia M.; Ssebuliba, Timothy; Morrison, Susan A.; Muwonge, Timothy R.; Boyer, Jade; Bambia, Felix; Badaru, Josephine; Stein, Gabrielle; Mugwanya, Kenneth K.; Wyatt, Christina; Yin, Michael T.; et al. (Frontiers in Reproductive Health, 2024)
Introduction: Oral pre-exposure prophylaxis (PrEP) is recommended during pregnancy for at-risk cisgender women. Pregnancy is known to impede bone growth and tenofovir-based PrEP may also yield detrimental changes to bone health. Thus, we evaluated the effect of PrEP use during pregnancy on bone mineral density (BMD). Methods: We used data from a cohort of women who were sexually active, HIV-negative, ages 16-25 years, initiating DMPA or choosing condoms for contraception and enrolled in the Kampala Women’s Bone Study. Women were followed quarterly with rapid testing for HIV and pregnancy, PrEP dispensation, and adherence counseling. Those who became pregnant were counseled on PrEP use during pregnancy per national guidelines. BMD of the neck of the hip, total hip, and lumbar spine was measured using dual-energy x-ray absorptiometry at baseline and annually. We compared the mean percent change in BMD from baseline to month 24. Results: Among 499 women enrolled in the study, 105 pregnancies occurred in 90 women. At enrollment, the median age was 20 years (IQR: 19-21) and 89% initiated PrEP. During pregnancy, 67% of women continued using PrEP and PrEP was dispensed in 64% of visits. BMD declined significantly in women using PrEP during pregnancy compared to women who were not pregnant nor used PrEP: relative BMD change was -2.26% (95% CI: -4.63 to 0.11, p=0.06) in the femoral neck, -2.57 % (95% CI: -4.48 to -0.66, p=0.01) in total hip, -3.06 % (95% CI: -5.49 to -0.63, p=0.001) lumbar spine. There was no significant difference in BMD loss when comparing PrEP-exposed pregnant women to pregnant women who never used PrEP. Women who became pregnant were less likely to continue PrEP at subsequent study visits than women who did not become pregnant (adjOR: 0.25, 95% CI: 0.16-0.37, p<0.001). Based on pill counts, there was a 62% reduction in the odds of high PrEP adherence during pregnancy (adjOR=0.38, 95% CI: 0.27-0.58, p<0.001). Conclusion: Women who used PrEP during pregnancy experienced a similar reduction in BMD as pregnant women with no PrEP exposure, indicating that BMD loss in PrEP-using pregnant women is largely driven by pregnancy and not PrEP.